FRI0259 Ectopic lymphoid structures support epstein-barr virus persistence and autoreactive plasma cell infection in sjogren's syndrome salivary glands. (23rd January 2014) - Croia, C.; Serafini, B.; Tappuni, A.; Aloisi, F.; Sutcliffe, N.; Pitzalis, C.; Bombardieri, M.
Abstract : Background: The ubiquitous □-herpesvirus Epstein-Barr virus (EBV) infects B cells and modifies their differentiation programme leading to B cell activation and immortalization. Due to these unique properties, EBV has been suggested to play a role in rescuing autoreactive B cells and promoting autoimmunity. Although different evidences support a link between EBV infection and Sjogren's syndrome (SS), the exact role of EBV in SS pathogenesis remains elusive. Objectives: To investigate the potential role of EBV in SS pathogenesis by analysing EBV infection in the SS salivary glands and its relationship with ectopic lymphoid structures (ELS), in situ autoreactive plasma cell differentiation, autoantibody production and cytotoxic immune response in the salivary glands. Methods: Latent and lytic EBV infection was investigated in SS and non-specific chronic sialoadenitis (NSCS) labial salivary glands characterised for presence/absence of ELS by RT-PCR, in situ hybridization and immunohistochemistry/immunofluorescence. Glandular production of anti-Ro52 antibodies and anti-EBV peptides antibodies was investigated in situ and/or in vivo in a novel SCID/SS chimeric model. Results: EBV dysregulation was observed exclusively in ELS+ SS salivary glands as revealed by presence EBV-encoded small RNA (EBER) transcripts and EBER+ cells and immunoreactivity for EBV latent (LMP1, LMP2A) and lytic (BFRF1) antigens in ELS-associated B cells and plasma cells, respectively. Importantly, a subset of EBV+ peri-follicular plasma cells produced anti-Ro52 antibodies. Furthermore, ELS-containing SS salivary glands transplanted into SCID mice supported the production of anti-Ro52, anti-La and anti-EBV antibodies. Analysis of CD4+ and CD8+ T-cell localization and granzyme B expression suggested that EBV persistence in ELS-containing SS salivary glands is favoured by exclusion of CD8+ T cells from B-cell follicles and impaired CD8-mediated cytotoxicity. Conclusions: We demonstrated latent and active EBV infection within ELS in the SS salivary glands that appears to contribute to local growth and differentiation of autoreactive B cells producing SS-associated autoantibodies. Disclosure of Interest : None Declared